Hierarchical description and analysis of CNN algorithms - Müller, Jens; Müller, Jan; Tetzlaff, Ronald (Proceedings (International Workshop on Cellular Neural Networks and Their Applications), 2014)
When designing algorithms, several implementations are often feasible, performing differently on the hardware. We introduce a formalism to hierarchically describe CNN-based algorithms, aimed at an execution on a CNN Universal Machine. Apart from the mere description, the formalism facilitates performance estimation and programming of the algorithms.